Polymeric Frustrated Lewis Pairs - Wang, Meng (The University of Edinburgh, 2019)
Frustrated Lewis Pair (FLP) chemistry is a significant and growing field since it offers a novel non-metal catalyst for hydrogenation and small molecule activation. Once it was discovered, different FLPs with varying reactivity towards small molecules have been extensively investigated. Its research has mainly focused on small molecule-based FLPs, however, especially in the aspect of hydrogenation reactions. In the field of polymer chemistry, several examples of conventional Lewis pair adduct containing polymers have been reported but there has yet been no exploration of FLPs incorporated into polymers up to the date of this project. Dynamic crosslinked polymeric networks have attracted more attention in recent years as their shape can be post-modified after polymerisation due to their exchangeable crosslinks. This dynamic crosslinking also makes the material stimuli-responsive and provides self-healing properties. This thesis introduces the synthesis of a polymeric network with combined features of frustrated Lewis pairs and dynamic crosslinking. New monomers containing Lewis acid or Lewis base centres were designed and synthesised successfully. For the pair 4- styryl-diphenylborane and 4-styryl-diphenylphosphine, the two monomers were found to be able to bind together at high concentration in toluene so as to form a weak conventional Lewis pair (CLP) adduct. An FLP can be obtained when the phosphine monomer was replaced to its more hindered analogue, 4-styryl-dimesitylphosphine, which is reactive enough to form a complex with diethyl azodicarboxylate (DEAD), where the DEAD bridges the boron and phosphorous centres. The monomers obtained were copolymerised with styrene by RAFT polymerisations. It was also found to be possible to control both the molecular weight and the dispersity. The FLP polymers synthesised in this way were characterised by NMR spectroscopy and gel permission chromatography. The Lewis acidity of both the monomer and resultant polymer were tested using the Gutmann-Beckett Method, and a decrease in Lewis acidity was observed when the boron monomer was polymerised. The network was synthesised by addition of DEAD into the solution containing both Lewis acid and Lewis base polymers. A gel was quickly generated (in 10 seconds). The mechanical properties of the network formed were determined by rheology. The gel was responsive to heat, in that it would break and return to a polymer solution at high temperatures. The gel formed also shows the ability to self-heal with the assistance of a solvent after physical cracking. The synthesis of the next generation of polymeric FLPs was also examined. A much more Lewis acidic boron monomer, (2,3,5,6-tetrafluorostyryl)- bis(pentafluorophenyl)borane was synthesised. This boron monomer was paired with 4-styryl-dimesitylphosphine to form a reactive FLP that was able to activate small molecules, including dihydrogen molecules and carbon dioxide. The catalysis reactivity of the hydrogenation reactions of this FLP was also explored. The copolymers made from these reactions readily formed a supramolecular gel upon mixing, which also proved temperature responsive. These early-stage results proved that this new boron-monomer is capable of generating a novel stimuli-responsive smart polymer for carbon capture and hydrogenation catalysis. Except for the polymeric FLP, some early-stage research about polymeric CLP and novel synthetic methods for boron-monomers were also introduced and discussed.
Keywords: dynamic crosslinked polymer materials; frustrated Lewis pairs; macromolecular FLPs; 4-styryl-dimesitylphoshine; 4-styryl-diphenylborane; polymer network synthesis